A Questionnaire-based Study on Impression Materials and Techniques for Complete Denture Construction among Dentists Practicing in Central/Western Regions of Libya - Albeshti, Rawan; Khmaj, Mofida; Khmaj, Abdulfatah; Albaden, Aihab; Almagtof, Hoda (Libyan Journal of Dentistry, 2024)
Background: The success of complete dentures mainly depends on impression-making accuracy; thus, dentists need to select the proper impression materials and techniques to achieve optimal outcomes. Objective: To determine the favoured impression materials and techniques used for complete denture construction among dentists practicing in the Central/Western regions of Libya. Materials and Methods: This study was conducted between July 2023 and September 2023. The questionnaire was comprised of 30 questions, which were divided into two parts including; 11 questions for demographic and professional attitude and 19 questions focused on professional steps of complete denture fabrication for edentulous patients. Results: The response rate for this questionnaire was (66%). It was revealed that (96.1%) of respondents used only irreversible hydrocolloid (alginate) as an ideal option for primary impressions. In response to the same question for final impressions, (45.8%) of participants exhibited that polyvinylsiloxane was the favourite choice. Regarding custom trays, (41.7%) of practitioners preferred using light-cured acrylic resin as a custom tray to take definitive impressions. (87.4%) of prosthodontists border molded the custom tray in sections by (81.9%), using modelling plastic impression compound by (92.1%). The most used philosophy for final impression making was the mucostatic impression technique by (50.4%), while (37.0%) used selective pressure and (12.6%) selected muco-compressive. Implant-supported overdenture was discussed as an alternative treatment by (65.4%). The obtained data was statistically analyzed using SPSS 28. Conclusion: This study reflects a diversity of opinion among Libyan dentists during the construction of complete dentures. The most commonly used material for primary impression was irreversible hydrocolloid (alginate) and for final impression was polyvinylsiloxane, which coincides with professional practices worldwide. Modelling plastic impression compound was the most preferred material for border molding. The mucostatic technique was the predominantly used impression philosophy for final impression making.